A high-strength and toughness titanium alloy and its preparation method and application

By introducing specific element combinations and laser selection melting 3D printing technology into titanium alloys, the problem of insufficient plasticity and work hardening performance of titanium alloys is solved, and high strength, high plasticity and good work hardening capabilities are prepared, suitable for Applications with complex structures and high performance requirements.

CN118406932BActive Publication Date: 2024-12-24NANCHANG HANGKONG UNIVERSITY +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410538944.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-30
Publication Date
2024-12-24
Estimated Expiration
2044-04-30

AI Technical Summary

Technical Problem

When the existing additive manufacturing technology prepares titanium alloys, the plasticity of titanium alloys is low, which limits its application in components. The titanium alloys prepared by traditional processes are insufficient in terms of work hardening performance.

Method used

A titanium alloy formula including 6% Al, 8.8-12% Nb, 0.3-0.4% Si and balance Ti is used to prepare high-strength tough titanium alloy through mechanical stirring and laser selection melting 3D printing technology to improve its plasticity and work hardening performance.

Benefits of technology

It has achieved high strength and high plasticity and has good mechanical properties, including room temperature yield strength, tensile strength and uniform elongation, and is suitable for aviation, aerospace and deep-sea exploration and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118406932B_ABST
    Figure CN118406932B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of titanium alloys, and specifically relates to a high-strength and toughness titanium alloy, a preparation method thereof and an application thereof. The high-strength and toughness titanium alloy provided by the present invention comprises the following element components in percentage by mass: 6% Al, 8.8-12% Nb, 0.3-0.4% Si and the balance Ti. In the present invention, Nb as a β-stabilizing element of the Ti alloy can increase the content of the β phase in the alloy, so that the alloy produces a plasticity-induced martensite effect during deformation, thereby improving the plasticity of the alloy; the Nb element can also increase the solubility and solid solution stability of Si. The present invention improves the plasticity and work hardening ability of the titanium alloy under the combined action of specific contents of Al, Nb, Si and Ti. It can be seen from the test results that the high-strength and toughness titanium alloy of the present invention has a yield strength of 865-1077MPa at room temperature (about 25°C), a tensile strength of 1210-1321MPa, and a uniform elongation of 5.6-6.9%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of titanium alloys, and in particular relates to a high-strength and toughness titanium alloy and a preparation method and application thereof. Background Art

[0002] The emerging additive manufacturing technology is different from traditional subtractive processing (such as machining) and equal material processing (such as forging). Its processing method belongs to additive manufacturing, and its forming process is to stack materials layer by layer to finally form a formed part. Additive manufacturing technology has advantages that traditional processes do not have: (1) Because additive manufacturing uses a layer-by-layer stacking method to manufacture products, it can produce exquisitely structured and complex formed parts; (2) The material utilization rate can be close to 100% (excluding supports), avoiding waste of materials and energy, and saving costs; (3) Integrated printing of assembly parts effectively avoids assembly errors between samples that lead to poor performance of assembly parts; (4) The product R&D and manufacturing cycle is short, and it does not require the manufacture of a casting mold first, like traditional processing techniques such as casting (this greatly prolongs the product manufacturing cycle). Selective Laser Melting (SLM) technology is a type of additive manufacturing technology. Its main processing method is to irradiate the sample with its high-energy laser beam to melt and solidify the powder sample layer by layer. Precisely because this technology can generate a very high-energy laser beam, it has good processing capabilities for some metals and ceramic powders with high melting points and high hardness. Selective laser melting technology has been widely used in the preparation of metal materials and ceramic materials.

[0003] At present, there are no more than 15 types of titanium alloys that can be prepared by additive manufacturing, and most titanium alloy powders are developed based on the original cast or forged titanium alloys, which to a certain extent limits the development of additive manufacturing technology. In addition, due to the rapid melting characteristics of the additive manufacturing process, the plasticity of the prepared titanium alloy is often low. Therefore, in order to further expand the application of additive manufacturing technology in the preparation of titanium alloy components, it is urgent to develop titanium alloys with higher plasticity and work hardening properties. Summary of the invention

[0004] In view of this, the present invention provides a high-strength and toughness titanium alloy and a preparation method and application thereof. The titanium alloy provided by the present invention has high plasticity and work hardening performance and can be used to prepare titanium alloy components using an additive manufacturing process.

[0005] In order to solve the above technical problems, the present invention provides a high-strength and toughness titanium alloy, comprising the following element components in percentage by mass:

[0006]

[0007] Preferably, the following element components are included in percentage by mass:

[0008]

[0009] Preferably, the following element components are included in percentage by mass:

[0010]

[0011] The present invention also provides a method for preparing the high-strength and toughness titanium alloy described in the above technical solution, comprising the following steps:

[0012] Mixing titanium powder, niobium powder, aluminum powder and silicon powder to obtain a mixed material;

[0013] The mixed material is 3D printed to obtain the high-strength and toughness titanium alloy.

[0014] Preferably, the average particle size of the titanium powder, niobium powder, aluminum powder and silicon powder is independently 15 to 53 μm.

[0015] Preferably, the mixing is carried out under the condition of mechanical stirring, the rotation speed of the mechanical stirring is 60 to 90 r / min, and the time of the mechanical stirring is 1.5 to 2.5 h.

[0016] Preferably, after the mixing, the further step includes: drying the mixed system to obtain a mixed material; the drying temperature is 90 to 110° C., and the drying time is 1.8 to 2.2 hours.

[0017] Preferably, the 3D printing includes laser selective melting printing.

[0018] Preferably, when the equipment used for laser selective melting printing is BLT-S210, the printing parameters are as follows: laser power 155w, scanning speed 1200mm / s, layer thickness 0.03mm, scanning spacing 0.1mm, scanning rotation increment 67°.

[0019] The present invention also provides applications of the high-strength and toughness titanium alloy described in the above technical solution or the high-strength and toughness titanium alloy prepared by the preparation method described in the above technical solution in the fields of aviation, aerospace and deep-sea exploration.

[0020] The present invention provides a high-strength and tough titanium alloy, comprising the following element components in percentage by mass: 6% Al, 8.8-12% Nb, 0.3-0.4% Si and the balance Ti. In the present invention, Al, as an α-stabilizing metal element of the Ti alloy, plays a role in solid solution strengthening, improves the specific strength of the Ti alloy, and the low-temperature and high-temperature strength. In order to prevent the formation of α2 (Ti3Al) phase and cause the brittleness of the material, the present invention limits the mass content of Al in the titanium alloy to 6wt%. At the same time, adding an appropriate amount of Si to the titanium alloy can form dispersion strengthening and improve the strength of the alloy; Nb, as a β-stabilizing element of the Ti alloy, can increase the content of β phase in the alloy, so that the alloy induces TRIP effect (plastic induced martensite effect) during deformation, thereby improving the plasticity of the alloy; Nb element can also improve the solubility and solid solution stability of Si. The present invention improves the plasticity and work hardening ability of the titanium alloy under the combined action of the above-mentioned specific contents of Al, Nb, Si and Ti. The test results of the examples show that the high-strength and toughness titanium alloy provided by the present invention has a yield strength of 865-1077 MPa at room temperature (about 25° C.), a tensile strength of 1210-1321 MPa, and a uniform elongation of 5.6-6.9%. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 : are stress-strain curves of the titanium alloys of Examples 1 and 2 and Comparative Examples 5 and 6 at room temperature;

[0022] Figure 2 The stress-strain curves of the titanium alloys prepared in Comparative Examples 1 to 4 at room temperature;

[0023] Figure 3 The metallographic diagram of the high-strength and toughness titanium alloy prepared in Examples 1 and 2;

[0024] Figure 4 The SEM images of the high-strength and toughness titanium alloys prepared in Examples 1 and 2;

[0025] Figure 5 It is a work hardening rate curve diagram of the titanium alloys of Examples 1, 2 and Comparative Examples 1 to 4. DETAILED DESCRIPTION

[0026] The present invention provides a high-strength and toughness titanium alloy, comprising the following element components in percentage by mass:

[0027]

[0028] Calculated by mass percentage, the high-strength and toughness titanium alloy provided by the present invention includes 6% Al.

[0029] The high-strength and tough titanium alloy provided by the present invention comprises 8.8-12% Nb, preferably 9-11% by mass percentage. The present invention introduces niobium into the titanium alloy to improve the fracture elongation of the titanium alloy and the work hardening ability of the titanium alloy.

[0030] Calculated by mass percentage, the high-strength and toughness titanium alloy provided by the present invention includes 0.3-0.4% Si, preferably 0.3% or 0.4%.

[0031] Measured by mass percentage, the high-strength and toughness titanium alloy provided by the present invention includes a remainder of Ti.

[0032] The present invention also provides a method for preparing the high-strength and toughness titanium alloy described in the above technical solution, comprising the following steps:

[0033] Mixing titanium powder, niobium powder, aluminum powder and silicon powder to obtain a mixed material;

[0034] The mixed material is 3D printed to obtain the high-strength and toughness titanium alloy.

[0035] The present invention mixes titanium powder, niobium powder, aluminum powder and silicon powder to obtain a mixed material. In the present invention, the titanium powder is preferably spherical; the average particle size of the titanium powder is preferably 15 to 53 μm, more preferably 20 to 40 μm. In the present invention, the niobium powder is preferably spherical; the average particle size of the niobium powder is preferably 15 to 53 μm, more preferably 20 to 45 μm. In the present invention, the aluminum powder is preferably spherical; the average particle size of the aluminum powder is preferably 15 to 53 μm, more preferably 25 to 50 μm. In the present invention, the silicon powder is preferably spherical; the average particle size of the silicon powder is preferably 15 to 53 μm, more preferably 23 to 48 μm.

[0036] In the present invention, the mixing is preferably carried out under the condition of mechanical stirring; the rotation speed of the mechanical stirring is preferably 60 to 90 r / min, more preferably 70 to 80 r / min; the time of the mechanical stirring is preferably 1.5 to 2.5 h, more preferably 2 h.

[0037] In the present invention, after the mixing, it is preferred that the mixed system is dried to obtain a mixed material. In the present invention, the drying temperature is preferably 90 to 110°C, more preferably 100°C; the drying time is preferably 1.8 to 2.2 hours, more preferably 2 hours. In the present invention, the drying is preferably carried out in a vacuum dryer. The present invention can improve the fluidity of the mixed material through drying, which is beneficial to the subsequent 3D printing.

[0038] After obtaining the mixed material, the present invention performs 3D printing on the mixed material to obtain the high-strength and toughness titanium alloy. In the present invention, the 3D printing preferably includes laser selective melting printing (SLM). The present invention has no special requirements for the process conditions of the laser selective melting printing, as long as the density of the high-strength and toughness titanium alloy can reach more than 99.9%. In an embodiment of the present invention, when the equipment used for the laser selective melting printing is BLT-S210, the printing parameters are as follows: laser power 155w, scanning speed 1200mm / s, layer thickness 0.03mm, scanning spacing 0.1mm, scanning rotation increment 67°.

[0039] The present invention preferably obtains the corresponding titanium alloy component by one-step molding according to the structural dimensions required by the titanium alloy.

[0040] The present invention adopts 3D printing to prepare titanium alloy, which can avoid the macro-segregation of elements that occurs in traditional casting methods and is conducive to the homogenization of alloy components. Because 3D printing uses a layer-by-layer stacking method to manufacture products, it can produce beautifully structured and complex formed parts; the utilization rate of raw materials for 3D printing can be close to 100% (excluding supports), avoiding waste of materials and energy, and saving costs; and 3D printing is an integrated printing assembly, which effectively avoids the assembly error between samples that leads to poor performance of the assembly.

[0041] The present invention adopts the SLM additive manufacturing technology to prepare titanium alloy materials by in-situ alloying method, which has the following advantages: (1) SLM technology can adjust the alloy composition ratio within a large range by controlling the amount of powder mixing, and quickly realize the alloy composition design; (2) The energy density of the laser heat source output adopted by SLM technology is large, which can quickly melt the refractory metal powder and quickly solidify it in a short time, greatly reducing the macro segregation of alloy elements and making the alloy composition more uniform.

[0042] The present invention also provides applications of the high-strength and toughness titanium alloy described in the above technical solution or the high-strength and toughness titanium alloy prepared by the preparation method described in the above technical solution in the fields of aviation, aerospace and deep-sea exploration.

[0043] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0044] Example 1

[0045] Spherical titanium powder with an average particle size of 20 μm, spherical niobium powder with an average particle size of 20 μm, spherical aluminum powder with an average particle size of 25 μm and spherical silicon powder with an average particle size of 23 μm are mechanically stirred at a rotation speed of 80 r / min for 2 hours and then placed in a vacuum dryer for drying at 100° C. for 2 hours to obtain a mixed material; the mass percentage of aluminum in the mixed material is 6%, the mass percentage of niobium is 8.8%, and the mass percentage of silicon is 0.4%.

[0046] The mixed material was used as raw material for laser selective melting printing using BLT-S210 equipment to obtain titanium alloy; the printing parameters of the BLT-S210 equipment were: laser power 155w, scanning speed 1200mm / s, layer thickness 0.03mm, scanning spacing 0.1mm, and scanning rotation increment 67°.

[0047] Example 2

[0048] A titanium alloy was prepared according to the method of Example 1, except that the mass percentage of niobium in the mixed material was 12%, and the mass percentage of silicon was 0.3%.

[0049] Comparative Example 1

[0050] A titanium alloy is prepared according to the method of Example 1, except that the mass percentage of aluminum in the mixed material is 3.5%, the mass percentage of silicon is 0.5%, and the mass percentage of niobium is 0.

[0051] Comparative Example 2

[0052] A titanium alloy is prepared according to the method of Example 1, except that the mass percentage of aluminum in the mixed material is 4.1%, the mass percentage of silicon is 0.6%, and the mass percentage of niobium is 0.

[0053] Comparative Example 3

[0054] A titanium alloy is prepared according to the method of Example 1, except that the mass percentage of aluminum in the mixed material is 5%, the mass percentage of silicon is 0.7%, and the mass percentage of niobium is 0.

[0055] Comparative Example 4

[0056] A titanium alloy is prepared according to the method of Example 1, except that the mass percentage of aluminum in the mixed material is 6.1%, the mass percentage of silicon is 0.8%, and the mass percentage of niobium is 0.

[0057] Comparative Example 5

[0058] Titanium alloy TC4 is used as a comparative example.

[0059] Comparative Example 6

[0060] Pure titanium (CP-Ti) was used as a comparative example.

[0061] The mechanical properties of the titanium alloys in Examples 1 to 2 and Comparative Examples 1 to 4 were tested at room temperature (25° C.) according to GB / T228.1-2010, and the stress-strain curves were obtained as follows: Figure 1 and Figure 2 As shown, Figure 1 is the stress-strain curve of the titanium alloy of Examples 1 and 2 and Comparative Examples 5 and 6, Figure 2 The stress-strain curves of the titanium alloys prepared in Comparative Examples 1 to 4 are shown in Table 1. The yield strength, tensile strength, uniform elongation and the ratio of yield strength to tensile strength calculated from the stress-strain curves are shown in Table 1.

[0062] Table 1 Mechanical properties of titanium alloys in Examples 1 to 2 and Comparative Examples 1 to 6

[0063]

[0064]

[0065] The alloy has a higher uniform elongation and a smaller ratio of yield strength to tensile strength, and its work hardening ability is stronger. Figures 1-2 It can be seen that at room temperature (about 25°C), the high-strength and toughness titanium alloy provided by the present invention exhibits good mechanical properties. Although the room temperature tensile strength of the Ti-Al-Nb-Si alloy is lower than that of the Ti-Al-Si titanium alloy in Comparative Examples 3 and 4, its uniform elongation is higher, its plasticity is better, and its work hardening ability in the plastic deformation stage is relatively excellent.

[0066] The high-strength and tough titanium alloy prepared in Examples 1 and 2 was corroded with Koll's reagent for 2 minutes. The metallographic image of the corroded sample was obtained by observing it with a metallographic microscope. Figure 3 As shown. Figure 3 It can be seen that as the Nb element increases (the niobium content in the alloy of Example 2 is higher than that in the alloy of Example 1), the content of β phase (the white bright part in the figure is β phase) increases. The high-strength and toughness titanium alloys prepared in Examples 1 and 2 were observed using a scanning electron microscope to obtain SEM images, as shown in FIG. Figure 4 As shown. Figure 4 It can be seen that there are two phases: α′ martensite (acicular structure in the dark part) and β phase (bright part).

[0067] right Figure 1 and Figure 2 The data in the stress-strain curve of is processed (the tensile data of each alloy is plotted after the yield strength, and the curve is fitted and then differentiated) to obtain the work hardening rate curve, such as Figure 5As shown in the figure. As the tensile stress increases, the tensile curve of the alloy increases from the yield strength to the ultimate tensile strength stage; from reaching the tensile limit to the fracture stage, the tensile curve decreases. These two stages are reflected in the work hardening rate curve, showing a rapid decline stage and a relatively smooth stage after bending; the earlier the work curve bends, the higher the value of the relatively smooth stage after bending, which means the better the work hardening ability of the alloy. Figure 5 It can be seen that the titanium alloy provided in the present application has better work hardening ability than the titanium alloys of Comparative Examples 1 to 6.

[0068] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A high-strength and tough titanium alloy, characterized in that: Includes the following elemental components in mass percentage: Al 6%; Nb 8.8~12%; Si 0.3~0.4%; Ti remainder; The method for preparing the high-strength and toughness titanium alloy comprises the following steps: Mixing titanium powder, niobium powder, aluminum powder and silicon powder to obtain a mixed material; Performing 3D printing on the mixed material to obtain the high-strength and toughness titanium alloy; The high-strength and toughness titanium alloy has a yield strength of 865-1077 MPa, a tensile strength of 1210-1321 MPa, and a uniform elongation of 5.6-6.9% at room temperature of about 25°C.

2. The high-strength and toughness titanium alloy according to claim 1, characterized in that: Includes the following elemental components in mass percentage: Al 6%; Nb 8.8%; Si 0.4%; Ti margin.

3. The high-strength and toughness titanium alloy according to claim 1, characterized in that: Includes the following elemental components in mass percentage: Al 6%; Nb 12%; Si 0.3%; Ti margin.

4. The method for preparing the high-strength and toughness titanium alloy according to any one of claims 1 to 3, comprising the following steps: Mixing titanium powder, niobium powder, aluminum powder and silicon powder to obtain a mixed material; The mixed material is 3D printed to obtain the high-strength and toughness titanium alloy.

5. The preparation method according to claim 4, characterized in that: The average particle sizes of the titanium powder, niobium powder, aluminum powder and silicon powder are independently 15-53 μm.

6. The preparation method according to claim 4 or 5, characterized in that: The mixing is carried out under the condition of mechanical stirring, the rotation speed of the mechanical stirring is 60-90 r / min, and the time of the mechanical stirring is 1.5-2.5 h.

7. The preparation method according to claim 6, characterized in that: After the mixing, the method further comprises: drying the mixed system to obtain a mixed material; the drying temperature is 90-110° C. and the drying time is 1.8-2.2 hours.

8. The preparation method according to claim 4, characterized in that: The 3D printing includes laser selective melting printing.

9. The preparation method according to claim 8, characterized in that: When the equipment used for laser selective melting printing is BLT-S210, the printing parameters are as follows: laser power 155w, scanning speed 1200mm / s, layer thickness 0.03mm, scanning spacing 0.1mm, scanning rotation increment 67°.

10. Application of the high-strength and toughness titanium alloy according to any one of claims 1 to 3 or the high-strength and toughness titanium alloy prepared by the preparation method according to any one of claims 4 to 9 in the fields of aviation, aerospace and deep-sea exploration.